The role of the Spanish vowel system as a key factor in the accent of the English spoken by undergraduate students in their fourth and fifth academic year of the Foreign Language Department at the University of El Salvador, main campus, year 2017 - Alvarenga Miranda, Hugo Iván; Hernández Gómez, Ángel Josué (2024)
Globalization and English as the dominant language in the world have led most of the countries to adopt it as a requirement to be competitive in science, international trade, technology, the arts, etc. Blommaert (2010) observed that English language is intrinsically connected to the process of globalization; thus, the fact that two Anglophone nations, England and the United States of America, have played a significant role within the five continents throughout the last four centuries is the reason why English is the primary option when it comes to learning a foreign language. Furthermore, professionals from different areas have to learn English in order to keep their knowledge updated. Additionally, learning English grants more job opportunities and a wider range of choices for entertainment regarding music, movies, video games and literature. Thus, mastering the skills of speaking, listening, reading and writing English guarantees a diverse sort of advantages to people and those rewards motivate to overcome different difficulties and face challenges that might restraint them to reach the required proficiency level to communicate effectively in that foreign language. The constantly growing community of Latin Americans in the territory of the United States of America implies a considerable endeavor for the institutions of the host country and for the new comers who are demanded to be skillful in English in order to achieve their full integration. In addition to this, many Canadian and American companies have opened branches in the south of the American continent due to the free trade agreements they signed with countries of that region, which involves that Spanish speaking countries necessitate people who master English as a condition to take advantage of the new business and job opportunities. Also, the tourist industry is already a very important sector in the economy of several countries of Central and South America which means that all employees involved in that area have to speak English when dealing with tourists who are Anglophone. Consequently, native Spanish speaker population is in need to learn English either as a second or foreign language. Governments are implementing English language policies grounded partly in an economic rationale, propelled by a focus on building the proficiency of the population in part to boost a country’s competitiveness in a globally integrated market (British Council, 2017). Consequently, the number of native Spanish speakers who become Spanish- English bilinguals is expanding as a precondition to come up to the new challenges. Being an English speaker in El Salvador is an advantage when applying for a job. The call center industry has been permanently growing in El Salvador and the companies complete their staff by hiring Salvadorans who have studied English as a foreign language and those who learned it while living abroad. In addition to that, Salvadoran professionals are required English knowledge either to get a new job or to be promoted to a better position at their current job. This sort of boom of English language in the national territory has generated a bloom of language schools which demand teachers with native-like proficiency or at least a high level in English. Hence, mastering English language widens the range of job opportunities for Salvadoran population, yet people have to overcome some conditions that hinder to meet the requirements in regards to the proficiency level required by employers